Paleocene emergence of elephant relatives and the rapid radiation of African ungulates - (:unkn) unknown (My University, 2009)
Elephants are the only living representatives of the Proboscidea, a formerly diverse mammalian order whose history began with the 55-million years (mys) old Phosphatherium. Reported here is the discovery from the early late Paleocene of Morocco, ca. 60 mys, of the oldest and most primitive elephant relative, Eritherium azzou-zorum n.g., n.sp., which is one of the earliest known representatives of modern placental orders. This well supported stem pro-boscidean is extraordinarily primitive and condylarth-like. It provides the first dental evidence of a resemblance between the proboscideans and African ungulates (paenungulates) on the one hand and the louisinines and early macroscelideans on the other. Eritherium illustrates the origin of the elephant order at a previously unknown primitive stage among paenungulates and ''ungu-lates.'' The primitive morphology of Eritherium suggests a recent and rapid paenungulate radiation after the Cretaceous-Tertiary boundary, probably favoured by early endemic African paleoeco-systems. At a broader scale, Eritherium provides a new old calibration point of the placental tree and supports an explosive placental radiation. The Ouled Abdoun basin, which yields the oldest known African placentals, is a key locality for elucidating phylogeny and early evolution of paenungulates and other related endemic African lineages. Africa-Morocco ͉ Afrotheria ͉ Paenungulata ͉ Placentalia ͉ Proboscidea
Keywords: African Research